Proteomics Landscape Mapping of Organ‐Resolved Behçet's Disease Using In‐Depth Plasma Proteomics for Identifying Hyaluronic Binding Protein 2 Expression Associated With Vascular Involvement - Cheng, Linlin; Wang, Dongxue; Wang, Zhimian; Li, Haolong; Wang, Guibin; Wu, Ziyan; Xu, Meng; Yan, Songxin; Zhan, Haoting; Wang, Hongye; Zhang, Xiaomei; Liang, Te; et al. (Arthritis & rheumatology (Hoboken, N.J.), 2023)
Objective This study was undertaken to elucidate the pathogenesis and heterogeneity of Behçet's disease (BD) involving different organs using in‐depth proteomics to identify the biomarkers for clinical assessment and treatment of patients with BD. Methods We measured the expression levels of proteins in plasma samples from 98 patients with BD and from 31 healthy controls using our in‐depth proteomics platform with a data‐independent acquisition mass spectrometer and antibody microarray. We performed bioinformatics analyses of the biologic processes and signaling pathways that were changed in the BD group and constructed a proteomics landscape of organ‐resolved BD pathogenesis. We then validated the biomarkers of disease severity and the vascular subset in an independent cohort of 108 BD patients and 29 healthy controls using an enzyme‐linked immunosorbent assay. Results The BD group had 220 differentially expressed proteins, which discriminated between BD patients (88.6%) and healthy controls (95.5%). The bioinformatics analyses revealed different biologic processes associated with BD pathogeneses, including complement activation, wound healing, angiogenesis, and leukocyte‐mediated immunity. Furthermore, the constructed proteomics landscape of organ‐resolved BD identified proteomics features of BD associated with different organs and protein targets that could be used for the development of therapeutic treatment. Hyaluronic binding protein 2, tenascin, and serpin A3 were validated as potential biomarkers for the clinical assessment of vascular BD and treatment targets. Conclusion Our results provide valuable insight into the pathogenesis of organ‐resolved BD in terms of proteomics characteristics and potential biomarkers for clinical assessment and potential therapies for vascular BD.